2018
DOI: 10.5606/fng.btd.2018.009
|View full text |Cite
|
Sign up to set email alerts
|

Sexuality assessment: Nurses’ attitudes and beliefs toward sexuality

Abstract: Objectives: The aim of this study is to determine the nurses' assessment of the sexual health of the patients and their attitudes and beliefs about sexual health. Materials and methods: The study had a descriptive, cross-sectional design. The sample of this research was composed of nurses working in three central public hospitals in Antalya, Turkey. In the study, 492 nurses were reached and the study completed with 187 nurses who agreed to participate in the study. Study data were collected via "Personal Infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
1
0
2
Order By: Relevance
“…A more recent study found that nurses were homophobic at the rate of 77% (Dorsen, 2012). A study conducted in Turkey with 187 nurses reported that nearly half of them behaved differently according to the patients’ sexual orientation while fulfilling the sexual healthcare needs of patients (Gültürk, Akpınar, Şen, & Balcı, 2018). That study found that the nurses mostly stated that they would provide care for LGBTI people and would not see any harm in doing this.…”
Section: Discussionmentioning
confidence: 99%
“…A more recent study found that nurses were homophobic at the rate of 77% (Dorsen, 2012). A study conducted in Turkey with 187 nurses reported that nearly half of them behaved differently according to the patients’ sexual orientation while fulfilling the sexual healthcare needs of patients (Gültürk, Akpınar, Şen, & Balcı, 2018). That study found that the nurses mostly stated that they would provide care for LGBTI people and would not see any harm in doing this.…”
Section: Discussionmentioning
confidence: 99%
“…47,72±7,41 olarak bulmuş olup, puanlar bu çalışma sonuçlarına göre daha yüksektir. [19][20][21] hemşirelerin yaşı, cinsiyeti, evlilik durumu gibi faktörler nedeniyle farklılık gösterebilmektedir. 6,22 Hemşirelerin kanser hastalarında cinsel sağlığın değerlendirmesini öncelikli durum olarak görmemesi ve cinsel sağlık hakkında hastalarla iletişime geçmede kendilerini yeterli hissetmemesi nedeniyle cinsel bakıma ilişkin tutum ve inançlarının farklılık gösterdiği düşünülmüştür.…”
Section: Discussionunclassified
“…23 Cinsiyetin cinsel sağlık tutumu ile ilişkisinin olmadığını belirten çalışmalarda mevcuttur. 24,25 Cinsel sağlık bakımına yönelik tutum sadece bakım verenin cinsiyetine değil aynı zamanda bakım veren ile hasta arasındaki cinsiyet farklılığına da bağlıdır. 26 Öğrencilerin cinsel sağlık konusunda bilgilerinin yeterli olduğunu düşünmesi ve cinsel sağlık tutumu arasında anlamlı bir ilişki olduğu saptanmıştır.…”
Section: Verilerin Toplanması Ve Analiziunclassified